Offensive language used in interaction and its influence towards students’ language usage / Nur Miza Athira Mohd Samlan and Ilham Alia Mat Isa - Mohd Samlan, Nur Miza Athira; Mat Isa, Ilham Alia (Universiti Teknologi MARA Cawangan Kedah, 2022)
A meaningful interaction is the primary way of boosting language acquisition among second language learners while providing a platform for daily conversation. Language users should recognise the significance of each phrase uttered as it may leave positive or negative impacts on the language usage. With this in mind, the present study is meant to identify students’ perspectives on the factors influencing ESL students to use offensive words in their interaction and the effects of offensive language usage. The current study employed a qualitative research method, where semi-structured interviews were conducted by addressing the relevant questions to the participants. The data was then assembled and arranged to specific themes by applying thematic analysis method. According to the data obtained from the study, the participants were quite familiar with the use of profanity in their interaction under specific conditions. As per the findings, the underlying factors for a student's usage of profanity are most likely due to media exposure as well as peer pressure and the effects identified are emotion and ‘perceiving’. The results and findings of this study appear to be enlightening and comprehensive, which might assist people in the area of linguistics as well as the general public to be sensitive in uttering meaningful words in their daily conversation, hence shape younger generation’s interaction- the generation of our country’s future leaders.